Effect of native vitamin D3 supplementation on refractory chronic hepatitis C patients in simeprevir with pegylated interferon/ribavirin. Issue 5 (17th September 2015) - Atsukawa, Masanori; Tsubota, Akihito; Shimada, Noritomo; Yoshizawa, Kai; Abe, Hiroshi; Asano, Toru; Ohkubo, Yusuke; Araki, Masahiro; Ikegami, Tadashi; Okubo, Tomomi; Kondo, Chisa; Osada, Yuji; et al.
Abstract : Aim: Protease inhibitors with pegylated interferon (PEG IFN)/ribavirin improve a sustained virological response (SVR) rate to approximately 90% in chronic hepatitis C genotype 1b patients with IL28B rs8099917 genotype TT, but yield only approximately 50% in those with the unfavorable non‐TT. Among such treatment‐refractory patients, serum vitamin D levels could influence the SVR rate. This randomized controlled trial was conducted to assess the effect of native vitamin D supplementation in simeprevir with PEG IFN/ribavirin for 1b patients with non‐TT. Methods: Patients were randomly assigned to receive simeprevir (100 mg/day) for 12 weeks plus PEG IFN/ribavirin for 24 weeks (control group, n  = 58), or vitamin D (2000 IU/day) for 16 weeks including a lead‐in phase plus PEG IFN/ribavirin for 24 weeks (vitamin D group, n  = 57). The primary end‐point was sustainably undetectable viremia 24 weeks after the end of treatment (SVR). Results: SVR rates were 37.9% in the control group and 70.2% in the vitamin D group. In subgroup analysis, SVR rates of prior null responders were 11.8% and 54.5%, respectively. SVR rates for advanced fibrosis were 28.6% and 65.4%. SVR rates for patients with vitamin D3 deficiency at the baseline were 25.0% in the control group and 66.7% in the vitamin D group. Overall, the SVR rate was significantly higher in patients with high serum 25(OH)D3 levels at the beginning of combination therapy than in those with low serum 25(OH)D3 levels. Conclusion: Native vitamin D3 supplementation improved SVR rates in simeprevir with PEG IFN/ribavirin for chronic hepatitis C genotype 1b patients with refractory factors.